Functional connectivity of the brain in active professional football (soccer) players - Haase, F. K.; Feddermann-Demont, N.; Junge, A.; Welsch, G.; Schuenemann, C.; Fiehler, J.; Reinsberger, C. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Long-term consequences of heading associated repetitive head impacts (RHIs) in football (soccer) are an area of scientific debate with large clinical relevance. Functional magnetic resonance imaging (fMRI) based resting-state functional connectivity (FC) in intrinsic networks of semi-professional football players revealed increased FC within the default mode network (DMN) with large exposure to RHIs, but longitudinal fMRI investigations are still sparse. We therefore aimed to determine and evaluate potential FC changes in the DMN and the salience network (SN) in relation to heading in professional football players prospectively.